1993
DOI: 10.1901/jaba.1993.26-183
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis and Treatment of Multiply Controlled Self‐injury

Abstract: A functional analysis of the self-injurious behavior (SIB) of 3 adults with profound developmental disabilities showed that each engaged in SIB in more than one assessment condition. Such outcomes may result from a failure to isolate the variable maintaining SIB, or they may reflect multiple sources of control over SIB. In order to identify more dearly the determinants of SIB, each subject was exposed to a series of treatments appropriate to one or both of the apparent functions of SIB. These treatments, appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 17 publications
3
62
0
1
Order By: Relevance
“…These results join a small but important body of research emphasizing the contextual nature of behavior and documenting that problem behaviors may be maintained by multiple functions (Durand & Carr, 1992;Haring & Kennedy, 1990;Smith et al, 1993).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These results join a small but important body of research emphasizing the contextual nature of behavior and documenting that problem behaviors may be maintained by multiple functions (Durand & Carr, 1992;Haring & Kennedy, 1990;Smith et al, 1993).…”
Section: Discussionsupporting
confidence: 55%
“…Iwata, Dorsey, Slifer, Bauman, and Richman (1982) hypothesized that self-injurious behavior (SIB) may serve multiple functions for individuals whose behavior did not show dearly differentiated patterns. More recent data from over 150 cases support this hypothesis (Iwata et al, 1994), and the application of multiple baseline assessments has provided one approach for identifying multiply maintained responses (Smith et al, 1993). These results are further supported by Haring and Kennedy's (1990) demonstration that the function of a behavior may be affected by the context in which the behavior occurs.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Second, matching evaluations of problem behavior have not considered the possibility of multiply controlled problem behavior in an experimental analysis of consequent events (e.g., McDowell, 1981;Oliver et al, 1999). Several studies have shown that problem behavior reinforced by attention can be maintained by other sources of reinforcement, such as access to tangible stimuli or removal of instructed activities (e.g., Iwata, Pace, Dorsey, et al 1994;Piazza et al, 1997;Smith, Iwata, Vollmer, & Zarcone, 1993). Third, there has been an implicit assumption that reinforcement rate drives (i.e., controls) response rate.…”
mentioning
confidence: 99%
“…In addition, children that engage in problem behavior that is multiply-maintained may require more than one treatment. If this is the case for both children, this may require a caregiver to master several interventions at one time (e.g., Borrero & Vollmer, 2006, Day, Horner, & O'Neill, 1994Ingvarsson, Kahng, & Hausman, 2008;Lalli & Casey 1996;Smith, Iwata, Vollmer, & Zarcone, 1993). When considering which child to treat first, it may be the case that the more severe problem behavior requires more intensive interventions or may be more resistant to treatment.…”
Section: Pre-admission Planningmentioning
confidence: 99%